1997
DOI: 10.1080/713755707
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Short Term Recognition Memory for Tones: Streaming or Interference?

Abstract: A sequence of auditory stimuli interpolated between the initial presentation of a tone and a comparison tone impairs recognition performance. Notably, the impairment is much less with interpolated speech than with tones. Six experiments converge on the conclusion that this pattern of impairment is due more to the organization of the interpolated sequence than to its similarity to the to-be-remembered standard. Factors that contribute to the coherence of the interpolated sequence into a stream distinct from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 19 publications
2
27
1
Order By: Relevance
“…ticipant 4 actually showed a reliable difference between the two intervals for this distractor. None of the group analyses reached significance, which contradicts earlier studies that found that discrimination accuracy reliably improved when the distractor tone sequence was temporally removed from the standard (e.g., Berti et al, 2006;Jones et al, 1997;Massaro, 1970). It is plausible that the improved performance after longer intervals documented by both Massaro (1970) and Berti et al resulted partially from additional encoding time rather than from consolidation.…”
Section: Resultscontrasting
confidence: 79%
See 3 more Smart Citations
“…ticipant 4 actually showed a reliable difference between the two intervals for this distractor. None of the group analyses reached significance, which contradicts earlier studies that found that discrimination accuracy reliably improved when the distractor tone sequence was temporally removed from the standard (e.g., Berti et al, 2006;Jones et al, 1997;Massaro, 1970). It is plausible that the improved performance after longer intervals documented by both Massaro (1970) and Berti et al resulted partially from additional encoding time rather than from consolidation.…”
Section: Resultscontrasting
confidence: 79%
“…For instance, Massaro (1970), Jones et al (1997), and Berti et al (2006) all required participants to make judgments on the basis of pitch, whereas the present experiment relied on listeners detecting a difference in spectral timbre. To further explore these data, we conducted a Q (see Michael, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ueda (2004) noted that perceptual similarity, ostensibly so critical to interference, is actually very closely related to perceptual organization, and Jones, Macken, and Harries (1997) have suggested that "interference" in auditory memory may essentially reflect the degree to which the standard and distractors are perceptually integrated or grouped. The likelihood of grouping is heavily dependent on the auditory context in which sounds occur, particularly the temporal context (see Snyder, Carter, Lee, Hannon, & Alain, 2008;Winkler et al, 2003), and Jones et al recognized that the temporal arrangement of the typical interpolated-tone paradigm task may have established a context extremely favorable for the operation of grouping since many studies employing this procedure used an interval between the standard and first distractor, which was identical to that separating the distractor tones themselves (often 300 msec; e.g., Deutsch, 1970;Starr & Pitt, 1997).…”
mentioning
confidence: 99%